Incorporation of redox-activity into metal-organic frameworks for enhanced supercapacitors: A review - Otun K.O.; Mukhtar A.; Nafiu S.A.; Bello I.T.; Abdulsalam J. (Elsevier Ltd, 2025)
Metal-organic frameworks (MOFs) have gained significant research attention in recent times as electrode materials for energy storage devices due to their high porosity, high chemical and structural tunability, and excellent textural properties. However, one of the key drawbacks to the applications of MOFs as electrodes for energy storage is their low electrical conductivity induced by the insulating nature of most organic linkers and the low overlap between conjugated -orbitals of the linkers and/or the d-orbitals of transition metals which define the structures of MOFs. A variety of approaches that mostly preserve the intriguing properties of MOFs have been established to impart redox activity into MOFs to improve their electrochemical performance such as redox hopping/electron self-exchange between fixed sites, covalent incorporation of redox active mediators, imparting bandlike electronic conductivity, among others. As a result, this review discusses recent advances in the strategies to prepare redox-active MOFs with targeted properties including electrical conductivity, ionic conductivity, stability, and porosity to maximize their potentials in the fabrication of supercapacitor devices with excellent performance. Along with a critical analysis of the reported performances of conductive and redox-active MOFs for supercapacitors, their energy and charge storage mechanisms are discussed. Finally, a brief outlook to the future research directions is outlined for advancing MOF research for electrochemical energy storage applications. ? 2024 Elsevier Ltd